Expression and prognostic relevance of CRP, PCT, and ll-15 in patients with postoperative infection due to spinal injury: CRP, PCT, and ll-15 in postoperative infection - Chen, Xin; Liu, Xiangge; Yuan, Zhirui; Zhang, Zhanqi (Cellular and Molecular Biology, 2022)
C-reactive protein (CRP), procalcitonin (PCT), interleukin-15 (ll-15) expression and prognostic relevance were analyzed in patients with postoperative infection due to spinal injury. For this purpose, a total of 169 cases of spinal injury patients who underwent surgical treatment from July 2021 to July 2022 were selected, and the patients were divided into the uninfected group (148 cases), infected group (21 cases) according to the presence or absence of infection after surgery. Looking at the site of infection in both groups, the levels of CRP, PCT, and ll-15 in the two groups were detected using an enzyme-linked immunosorbent assay, and the expression of the three in postoperative infection of spinal injury and the correlation with prognosis were analyzed. Results showed that compared with the uninfected group, the infected group had higher levels of CRP, PCT, and ll-15, which were different (P < 0.05). There were no significant differences in the CRP levels between the superficial infection of the incision and the deep infection of the incision as well as other systemic infection populations at 1 d after surgery (P >0.05). CRP levels were higher in the group with deep infection of the incision as well as other systemic infections compared to the group with superficial infection at 3D and 7d after surgery (P < 0.05). There were no significant differences in the level of PCT between patients with superficial infection of the incision and those with deep infection of the incision as well as other systemic infections at 1 d after surgery (P > 0.05). The level of PCT was higher in the population with deep infection of incision as well as other systemic infections compared to the population with superficial infection at 3D and 7d after the operation (P<0.05). There were no statistically significant differences in the levels of ll-15 between patients with superficial infection of the incision and those with deep infection of the incision as well as other systemic infections at 1 D postoperatively (P>0.05). At 3D and 7d postoperatively, compared to the population with superficial incisions, the population with deep incisions as well as other systemic infections had higher levels of ll-15 with statistical significance (P < 0.05). CRP and PCT showed a positive correlation (r=7.192, P=0.001). CRP, ll-15 showed a positive correlation (r = 5.231, P = 0.001). PCT, ll-15 showed a positive correlation (r=9.029, P=0.001). CRP, PCT, ll-15 levels are closely related to postoperative infection in spinal injury. CRP, PCT, ll-15 showed high expression in postoperative infection of spinal injury and compared with the infection of the superficial part of the incision, the infection of the deep part of the incision, other systems have higher levels of CRP, PCT, ll-15. Moreover, CRP, PCT, and ll-15 were significantly associated with prognosis.